Phân tích đa thức thành nhân tử:
\(a,x^2-4x+3\)
\(b,x^4+4\)
\(c,\left(x^2+x\right)^2+4x^2+4x-12\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a)\(\frac{x^3-x}{3x+3}=\frac{x.\left(x^2-1\right)}{3.\left(x+1\right)}=\frac{x.\left(x-1\right).\left(x+1\right)}{3.\left(x+1\right)}=\frac{x.\left(x+1\right)}{3}=\frac{x^2+x}{3}\)
\(5x^3-10x^2y+5xy^2\)
=\(5x\left(x^2-2xy+y^2\right)\)
=\(5x\left(x-y\right)^2\)
a, x^2-4x+3
=x^2-x-3x+3
=x(x-1)-3(x-1)
=(x-3)(x-1)
\(\left(x^2+x\right)^2+4x^2+4x-12\)
\(=x^4+2x^3+5x^2+4x-12\)
\(=x^4-x^3+3x^3-3x^2+8x^2-8x+12x-12\)
\(=x^3.\left(x-1\right)+3x^2.\left(x-1\right)+8x.\left(x-1\right)+12.\left(x-1\right)\)
\(=\left(x-1\right).\left(x^3+3x^2+8x+12\right)=\left(x-1\right).\left(x+2\right).\left(x^2+x+6\right)\)
p/s: sai sót bỏ qua